General Psychopathology, Cognition, and the Cerebral Cortex in 10-Year-Old Children: Insights From the Adolescent Brain Cognitive Development Study - Patel, Yash; Parker, Nadine; Salum, Giovanni A.; Pausova, Zdenka; Paus, Tomáš (Frontiers in Human Neuroscience, 2022)
General psychopathology and cognition are likely to have bi-directional influence on each other. Yet, the relationship between brain structure, psychopathology and cognition remains unclear. This brief report investigates the association between structural properties of the cerebral cortex (surface area, cortical thickness, intra-cortical myelination indexed by T1w/T2w ratio, and neurite density assessed by restriction spectrum imaging) with general psychopathology and cognition in a sample of children from the Adolescent Brain Cognitive Development (ABCD) study. Higher levels of psychopathology and lower levels of cognitive ability were associated with smaller cortical surface area. Inter-regionally – across the cerebral cortex – the strength of association between area and psychopathology is strongly correlated with the strength of association between area and cognition. Taken together, structural deviations particularly observed in cortical surface area influence both psychopathology and cognition.